2014
DOI: 10.3390/s140610024
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Patterns of Apparent Electrical Conductivity: DUALEM vs. Veris Sensors for Monitoring Soil Properties

Abstract: The main objective of this study was to compare two apparent soil electrical conductivity (ECa) sensors (Veris 2000 XA and DUALEM 1S) for mapping variability of soil properties in a Mediterranean shallow soil. This study also aims at studying the effect of soil cover vegetation on the ECa measurement by the two types of sensors. The study was based on two surveys carried out under two very different situations: in February of 2012, with low soil moisture content (SMC) and with high and differentiated vegetatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…1d) using iso‐cluster unsupervised classification in ArcGIS 10.4 (ESRI). The EM measurements can be used as an indicator of the variation in surface elevation because the topography affects the soil characteristics and the formation of the pedological units (e.g., soil texture and thickness of horizons); consequently, these changes are reflected in electrical conductivity (EC) measurements (Serrano et al, 2014). The optimum number of clusters (subareas) was determined using as criterion the existence of a minimum number of bulk and undisturbed soil samples that could be used to characterize each subarea.…”
Section: Methodsmentioning
confidence: 99%
“…1d) using iso‐cluster unsupervised classification in ArcGIS 10.4 (ESRI). The EM measurements can be used as an indicator of the variation in surface elevation because the topography affects the soil characteristics and the formation of the pedological units (e.g., soil texture and thickness of horizons); consequently, these changes are reflected in electrical conductivity (EC) measurements (Serrano et al, 2014). The optimum number of clusters (subareas) was determined using as criterion the existence of a minimum number of bulk and undisturbed soil samples that could be used to characterize each subarea.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding Earth resistance contact sensors, experimental work has stressed their greater suitability for PA. It has been observed that these sensors have a greater temporal stability in the correlation of ERa values and soil properties under varying conditions of moisture and vegetal ground cover (Serrano et al ., : 10038). On the downside, bigger size and weight requires pulling them with a tractor, and therefore are limited by the size and shape of the land plots.…”
Section: Introductionmentioning
confidence: 97%
“…More recently the work by Serrano et al . () deals with the response of shallow and eroded Mediterranean soils in Portugal. Obviously the election of a specific method and equipment depends on the research objectives and characteristics of terrain.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneity in soil properties with depth and across landscapes can be accounted for by several interacting factors that operate with different intensities and at different scales and acting simultaneously [3]. Estimating spatial variability of soil properties is important for evaluating environment [4] and provides the factors and processes controlling potential in agriculture production [5].…”
Section: Introductionmentioning
confidence: 99%